Urban design and climate change with emphasis on energy - Lorimer, Stephen (AESOP, 2010)
In the context of climate change urban design has a dual role to try to limit and adapt to the consequences of climate change. The role of urban design may have been neglected because it deals with a complex set of dependent parts which are hard to quantify. Understanding urban design and climate change means looking beyond the merely technical solutions that deliver energy to meet demand with less carbon emissions. Urban designers are well placed to reassess the patterns of living and building which have turned an energyhungry modern world into a physical reality. One of the role of urban design is to assist in adapting the built environment to climate change resulting from global temperature rises due to greenhouse gas emissions occurring due to human activity on the planet. Urban design can be an enabler for other disciplines to reduce energy and material consumption – making the job of campaigners, architects, and engineers easier and in some cases even possible at the sharp end of the fight to limit climate change.
Book of proceedings: Urban change : The prospect of transformation